Optimizing the Role of Productive Waqf in Realizing the Welfare of the People of Palu City - khairunnisa; Nurdin, Nurdin; Malkan, Malkan (State Islamic University Datokarama Palu, 2024)
This article discusses optimizing the role of productive waqf in Palu City and the factors inhibiting maximizing the role of productive waqf in the welfare of the people of Palu City. This research uses empirical legal research with a qualitative approach. The data collection technique is by direct observation at the Indonesian Waqf Board in Palu City, then by conducting interviews and documentation to complete the research information. The data analysis techniques used are data reduction, data presentation, and conclusion from general to specific. The results of this research explain that the optimization of productive waqf operations in Kolta Palu is carried out in various ways to promote community welfare, namely continuous socialization. Activities are also deliberately carried out to ensure the existence of new wakifs (waqf). Asset mobilization means looking for ways to consolidate public assets into waqf assets. The Indonesian Waqf Board has increased the capacity of recipients of waqf assets (Nazir). They will be trained and developed by the Indonesian Waqf Board to manage the waqf assets that have been allocated. Second, productive waqf in Palu has so far not been running optimally, and this collaboration is due to several contributing factors, namely the problem of the community's understanding of waqf procedures, waqf administration and management, waqf property, waqf nazir and budget funds for registration of land certificates.